DISTRIBUTION OF IRIDIOD GLUCOSIDES AND ANTI-OXIDANT COMPOUNDS IN SPATHODEA CAMPANULATA PARTS - Elusiyan, C. A.; Ani, N. C.; Adewunmi, C. O.; Olugbade, T. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
The antioxidant principles isolated from the various parts of the plant are verminoside (leaf, stem bark and flowers; EC50 = 2.04 µg/ml), Specioside (flowers; EC50 = 17.44 µg/ml), Kampeferol diglucoside (leaf; EC50 = 8.87 µg/ml) and Caffeic acid (leaf and fruits). The non anti-oxidant components isolated in the study include ajugol (stem bark and fruits) and phytol (leaf).